PRICE INFLUENCE, LOCATION AND QUALITY OF SERVICE TO CONSUMER SATISFACTION AT PUNCLUT NATURE TOURISM OBJECT AT BANDUNG - Dewi Anggaraeni, - (2009)
At this research there are four variables that is price, location quality of service and consumer satisfaction . Method applied is analytic descriptive method seeing two variables or more and that influence which then is done sampling from a population by using questionnaire as a means of data compiler. Population in this research is all consumer at Restaurant in Punclut Nature Tourism Object and becoming sample is consumer which that moment is residing in at Restaurant in Punclut Nature Tourism Object amount 94 consumers. Data collecting technique is conducted with questionnaire, interview and literature study. Intention of this research is to know price influence to consumer satisfaction, location influence to consumer satisfaction, influence service quality to consumer satisfaction and price influence, location and service quality to consumer satisfaction. From inferential data analysis and solution in simulate at freedom degree of 0,05 from all variables that is, price, location and service quality is influential to consumer satisfaction, and after conducted partially examination the price have positive influential, location doesn't have an effect and service quality have positive influential to consumer satisfaction at Restaurant in Punclut Nature Tourism Object.